2016
DOI: 10.4028/www.scientific.net/msf.879.1662
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effect during Electromagnetic Pulse Welding Process

Abstract: Magnetic pulse welding (MPW) is a solid state joining process, successfully utilized to join dissimilar metals. This advantage attracted manufacturing industries to fabricate hybrid materials to attain materials with a combination of multiple attributes. The high speed impact during the welding process causes various interfacial phenomena, which have been reported in previous research studies. Combined high speed collision, Joule heating due to eddy current and plastic heat dissipation cause noticeable heating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The coupling of the three physical fields of electromagnetic field, structure field and thermal field is involved in the process of MPW. Since the Joule heat generated by discharge is very small, the increase in temperature caused by Joule heat can be ignored [16]. Taking the MPW of an Al-Mg sheet as an example, this paper studies the electromagnetic field distribution of the capacitor bank discharge and the structural field of the Al sheet under the action of electromagnetic force.…”
Section: Simulation Schemementioning
confidence: 99%
“…The coupling of the three physical fields of electromagnetic field, structure field and thermal field is involved in the process of MPW. Since the Joule heat generated by discharge is very small, the increase in temperature caused by Joule heat can be ignored [16]. Taking the MPW of an Al-Mg sheet as an example, this paper studies the electromagnetic field distribution of the capacitor bank discharge and the structural field of the Al sheet under the action of electromagnetic force.…”
Section: Simulation Schemementioning
confidence: 99%
“…As the energy dissipates and the collision angle increases, the tremendous quantity of heat arising from severe plastic deformation, Joule heating, collision energy dissipation, and supersonic gaseous compression [20,31,32] give rise to the local melting in the weldingaffected zone or layer IV, accompanied by porous structures and splashed metal debris, as shown in Figure 5. In this stage, the surface tension of melt, dissolved or trapped air, instant high temperature, and pressure provoked by a high-velocity impact (being as high as 1000 m/s [23]) would affect the formation of porous structure and the further interfacial bonding.…”
Section: Microstructural Evolution and Formation Mechanismmentioning
confidence: 99%
“…Simulations and theoretical analyses were performed to understand the formation mechanism of such a morphology and succeeded in reproducing the wave morphology in the Al-Fe interface, and local melt was detected in the weld interface. Sapanathan et al [21] reported the 3D simulations of MP welds: one turn coil combined with a field shaper. The forecast temperature distributions show the phenomena of Joule heating and plastic heat dissipation.…”
Section: Introductionmentioning
confidence: 99%